A High Step-Up Multi-Input Boost Converter for Renewable Energy Systems - ขวัญอ่อน, สุดารัตน์; กองกาญจนะ, เกื้อกูล (Srinakharinwirot University Engineering Journal, 2018)
This paper proposes a multi-input high step-up boost converter topology for renewable energy system. The proposed converter provides a high voltage conversion ratio, approximately 20 times, in order to boost up the low input voltage generated from renewable energy sources about 20V – 40V to the high output voltage level of 400V. In addition, this proposed multi-input converter can employ with the multi-input sources to increase power to the load. In this paper, the configuration of the proposed converter and its principle of operation will be described. The converter parameters such as inductors and capacitors are designed to reduce the current and voltage ripples. The PI controller with one voltage control loop and multi current control loops is also designed to regulate the output voltage at the desired constant levels. The current control is based on the current weighting technique in order to provide the proper reference current for each current control loop. Simulation and experimental results show that the proposed high step-up multi-input boost converter can increase the voltage conversion ratio of 20. The PI controller based on the current weighting technique can satisfactorily regulate the output voltage at the desired constant levels under different operating conditions.